Evaluation of aromatic 6-substituted thienopyrimidines as scaffolds against parasites that cause trypanosomiasis, leishmaniasis, and malaria. Issue 2 (25th November 2014) - Woodring, Jennifer L.; Patel, Gautam; Erath, Jessey; Behera, Ranjan; Lee, Patricia J.; Leed, Susan E.; Rodriguez, Ana; Sciotti, Richard J.; Mensa-Wilmot, Kojo; Pollastri, Michael P.
Abstract : The repurposing of human tyrosine kinase inhibitor scaffolds for generation of antiparasitic agents has provided new lead compounds for tropical diseases. Abstract : Target repurposing is a proven method for finding new lead compounds that target Trypanosoma brucei, the causative agent of human African trypanosomiasis. Due to the recent discovery of a lapatinib-derived analog2 with excellent potency against T. brucei (EC50 = 42 nM) and selectivity over human host cells, we have explored other classes of human tyrosine kinase inhibitor scaffolds in order to expand the range of chemotypes for pursuit. Following library expansion, we found compound11e to have an EC50 of 84 nM against T. brucei cells while maintaining selectivity over human hepatocytes. In addition, the library was tested against causative agents of Chagas' disease, leishmaniasis, and malaria. Two analogs with sub-micromolar potencies for T. cruzi (4j ) and Plasmodium falciparum (11j ) were discovered, along with an analog with considerable potency against Leishmania major amastigotes (4e ). Besides identifying new and potent protozoan growth inhibitors, these data highlight the value of concurrent screening of a chemical library against different protozoan parasites.